Pre-experimental Study to Assess the Impact of Awareness Program on Knowledge Regarding Bio-medical Waste Management among Staff Nurses at Selected Hospital of Punjab - Sheikh, Masood Ahmad; Gavande, Swapna Vijay; Gavande, Sneha Vijay; Sharma, Jyoti; Cherian, Bincy (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of this study is to provide adequate knowledge and awareness among staff nurses reading bio-medical waste management. Introduction: Globally current waste and resource management lacks a holistic approach covering the whole chain of product design, raw material extraction, production, consumption, recycling, and waste management. About 85% waste is generated by health-care activities in general from non-hazardous waste and 15% is considered hazardous material that may be infectious, toxic, or radioactive. Methods: Pre-experimental design and 50 subjects were selected for this study. Structured knowledge questionnaire was used and analyzed by descriptive and inferential statistics using Chi-square and t-test. Results: The findings revealed that in post-test majority of the study subjects 43 (86%) had good knowledge, 7 (14%) had average knowledge and none of them had poor knowledge with post-test mean score (44.04 ± 6.141) is significantly higher than the mean pre-test knowledge scores (24.50 ± 8.428), with a mean difference of (19.540). Conclusion: Significant association of pre-test knowledge score with professional qualification (P = 0.000) while as no association was found between gender and years of experience with their pre-test knowledge scores (P > 0.05) at 0.05 level of significance.